TECHNOLOGY FOR COMBINING THE RESULTS OF 3D LASER SCANNING FROM DIFFERENT STATIONS USING PLANE MARKS - Batrakova, A.; Hunko, I.; Dorozhko, Ye.; Sarkisian, H.; Urdzik, S. (Municipal economy of cities (Technical science), 2024)
3D laser scanning is a promising technology gaining popularity and active use worldwide. One of the advantages of 3D laser scanning is the speed of the scanning process and processing of the results. Compared to other geodetic instruments, this technology allows for displaying large objects in a much shorter time and more efficiently. For example, at the construction stage of an industrial plant, scanning enables monitoring the shapes and sizes of all its elements in real time, which is critical for controlling and optimising construction processes. Another important aspect is the geometric complexity of objects. Many objects can have complex shapes or similar elements of considerable length. When combining scanning results from different stations, it is necessary to ensure the accuracy and correct geometry of the object. To combine scan results, designated markers in the form of spheres and plane marks are used. However, unlike spheres, plane markers can be more convenient and economical. In addition, they can be left on the object for a long time, which significantly simplifies the additional scanning or data correction. It is also notable that in our time, the development of laser scanning technologies has led to new scanners that can automatically stitch together scan results by using advanced technology to track characteristic points in the environment. Despite the significant advantages of this new technology in terms of efficiency and accuracy, it is worth noting that it is rather expensive. Accordingly, scanners that do not have this advanced technology rely on alternative methods of stitching together scan results, such as placing plane marks on the object. The article aims to develop a technology for combining the results of 3D laser scanning from different stations using plane marks. The article considers the evaluation of the technical characteristics of the Trimble TX6 laser scanner, the analysis of options for using plane marks to ensure scanning accuracy, and the identification of the advantages and disadvantages of this method.